Factors Relating to Teachers Followership in International Universities in Thailand - Ye, Yan (Scholar: Human Sciences, 2015)
The study was conducted to identify teachers’ followership styles; to identify the factors affecting teachers’ followership based on literature and expert interviews; to determine factors including Professionalism, Emotional Characteristics, Teamwork Attitudes, Department Climate, Satisfaction, Leadership Styles, and Teachers’ Development; and to determine the effects of these factors on teachers’ followership in international universities in Thailand. The examined population comprised 365 randomly selected instructors from the sample universities. The data was analyzed with regard to frequency, mean, standard deviation, and multiple regressions.The study found that in international universities in Thailand: (1) Followership styles from the most to the least frequent were pragmatist or exemplary followership, conformist followership, alienated followership and passive followership. (2) Teachers’ professionalism showed: the majority of teachers had master or doctoral degrees; 6-10 years teaching experience; academic positions were teacher; teaching the subject related very much to their major; they attended and presented papers at professional workshops, seminars, international conferences an average of once a year; conducted and published one study during the last 5 years; but most teachers haven’t written and published books or obtained any professional awards inside or outside of their university. (3) Teachers’ Emotional Characteristics were “good”. (4) Teachers’ Teamwork Attitudes: were “positive”. (5). Department Climate was “positive”. (6) Teachers’ Satisfaction was “satisfied”. (7) Teachers’ perception towards Development was “unclear about the professional development activities”. (8). Study on Leadership Styles showed: (A). most leaders were using Participative leadership, followed by Delegative leadership and Autocratic leadership. (B) .(a) To some extent; Autocratic leadership was likely to produce passive followers; (b) Participative leadership was likely to produce exemplary or pragmatist followers; and (c) Delegative leadership was likely to produce pragmatist or conformist followers. (9). The rank of significant variables contributing to teachers’ followership from high to low at .05 level of significance is: Professionalism, Emotional Characteristics, Satisfaction, Leadership Styles, Teamwork Attitudes, Department Climate, and Teachers’ Development. (10) The significant multiple correlation was .857 with the multiple coefficient of determination R Square=.735 or 73.5% of teachers’ followership could be explained by the prediction equation from the combined predictors, i.e.: Teachers’ Followership = .182 Leadership Styles + .422 Professionalism + .235 Emotional Characteristics + .131 Teamwork Attitudes -.121Department Climate + .211 Satisfaction + .073 Teachers’ Development (in standard score form)